Exploring the anticancer potential of Costus speciosus: a comprehensive review - I. S. Al-Dhuayan; M. M. Alnamshan; A. I. Alqosaibi; R. ElMazoudy; A. A. Al-Eidan; F. M. Alkhulaifi; N. F. AlAhmady; N. A. Alenezi; M. M. Almustafa; S. S. Al-Dossari (Brazilian Journal of Biology)
Abstract Costus speciosus is a medicinal plant with a long history in Indian Ayurvedic medicine, recognized for its diverse bioactive properties, including antibacterial, anticancer, anti-inflammatory, and antidiabetic effects. This review highlights its therapeutic potential, particularly in cancer treatment, where its bioactive compounds exhibit cytotoxic effects against breast, ovarian, and uterine cancers. These compounds have shown the ability to induce apoptosis, regulate the cell cycle, and inhibit cancer progression, offering a promising alternative to conventional chemotherapy with potentially fewer side effects. Additionally, C. speciosus demonstrates antioxidant, antimicrobial, and antidiabetic properties, expanding its clinical applications. Despite its promising pharmacological profile, further research is required to understand the molecular mechanisms underlying its therapeutic effects and ensure the safety and efficacy of its various extracts for therapeutic use.